Chemical composition and radical scavenging activity of Amygdalus pedunculata Pall leaves' essential oil. (September 2018) - Lu, Cairui; Li, Haoyu; Li, Cong; Chen, Bang; Shen, Yehua
Abstract: The main objective of the current study was to investigate the components and radical scavenging activity of essential oil from Amygdalus pedunculata Pall leaves (APEO) extracted by an ultrasound-assisted method. Thirty-eight chemical components were identified in APEO using gas chromatography-mass spectrometry (GC-MS). APEO primarily consisted of alcohols (36.82%), esters (28.81%), ketones (1.47%), alkanes (18.61%) and phenols (8.93%). The most abundant compound was n-hexanol (33.49%). The antioxidant activity of APEO was characterized for 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical, hydroxyl radical (OH·), hydrogen peroxide (H2 O2 ), and superoxide anion radical (O2 · - ) scavenging and Fe 3+ reduction, and the IC50 values were 2.32, 2.65, 2.42, 5.24 and 4.19 mg/mL, respectively. The IC50 values for H2 O2 scavenging and Fe 3+ reduction of APEO were less than those of ascorbic acid (Vc; 3.15 and 5.13 mg/mL). The results showed that APEO has a high radical scavenging activity. Graphical abstract: Highlights: Ultrasonic assisted extraction essential oil from Amygdalus pedunculata Pall leaves was first carried out. 38 compounds were identified by GC-MS, which contained important bioactive substances. The essential oil was found rich in eugenol and coumarin. The essential oil exhibited high free radical scavenging activity and total reduction ability.